The lithic industry in the Makapansgat Limeworks breccias and overlying surface soil - Maguire, Brian (Bernard Price Institute for Palaeontological Research, 1968)
The excavations directed by Professor Dart at the Makapansgat Limeworks, and conducted mainly by myself at the site since 1960, were concerned during the 1963- 1965 field seasons with an examination of the surface soil overlying the consolidated pink breccias, and of the contents of the abundant solution cavities which penetrate the underlying breccia mass to depths of up to 15 feet or more. The shallow soil , overlying and mainly derived from the consolidated australopithecine breccias, contains an abundance of crude artefacts which are largely composed of chert, a material native to the dolomitic cavern site. The most characteristic tools are various kinds of notched scrapers which are more particularly described. The undoubted relationship of these artefacts to those occurring in the underlying breccias is also discussed.
Main article
Keywords: Makapansgat; Limeworks; lithic; breccias; surface soil